Mineralization and Alteration of the Late Triassic Glacier Creek Cu-Zn VMS Deposit, Palmer Project, Alexander Terrane, Southeast Alaska - Steeves, Nathan (Université d'Ottawa / University of Ottawa, 2013)
The Glacier Creek volcanogenic massive sulfide (VMS) deposit is hosted within Late Triassic, oceanic back-arc or intra-arc, rift-related, bimodal volcanic rocks (Hyd or Tats Group) of the allochthonous Alexander terrane known as the Alexander Triassic Metallogenic Belt (ATMB). The deposit presently consists of four tabular massive sulfide lenses with a resource of 4.75 Mt. at 1.84% Cu, 4.57% Zn, 0.15% Pb, 0.28 g/t Au and 29.07 g/t Ag. A deposit-scale thrust fault offsets stratigraphy along the axial surface of a deposit-scale anticline. The massive sulfide lenses are barite-rich and are divided into 6 main ore-types based on mineral assemblages. There is a large range of sphalerite compositions, with low-Fe sphalerite dominant throughout the lenses and high-Fe sphalerite at the top and bottom of the lenses in pyrrhotite-rich zones. Lenses contain anomalous Sb, Hg and Tl. Gangue minerals include barite, quartz, barian-muscovite, calcite, albite, highly subordinate chlorite and locally hyalophane and celsian. Overlying massive sulfide is a tuffaceous hydrothermal sediment with anomalous REE patterns and local hyalophane. The general footwall to all four lenses is a thick unit of coherent to volcaniclastic feldspar-phyric basalt containing extensive lateral alteration. Four alteration facies are recognized based on mineral assemblages. Mass balance calculations for the footwall indicate general gains of S, Fe, Si and K with coincident loss of Ca, Na and Mg, along with trace element gains of Tl, Sb, Hg, Ba, Zn, Cu, As and loss of Sr with increased alteration intensity. Short wavelength infrared (SWIR) spectroscopy shows a general decrease in Na, K and Al content of muscovite and increase of Fe+Mg and Ba content towards ore. Integrated petrographic, mineral, chemical and sulfur-isotope data suggest a transition during deposit formation, from high-temperature, acidic, reduced hydrothermal fluids mixing with oxidized, SO4-rich seawater, to later cooler, low fO2-fS2 conditions of formation and a lack of SO4 in seawater.